The wrong man [large type] : a novel of suspense - White, Kate, 1950- (HarperLuxe, an imprint of HarperCollinsPublishers, 2015)
The New York Times best-selling author of Eyes on You and The Sixes delivers a story of mistaken identity and psychological suspense about Kit Finn, an accomplished career woman who thinks she's met the man of her dreams while visiting the Florida Keys?but instead finds her worst nightmare.